Monitoring for Amoebic Disease (Malpighamoeba mellificae) in Honey Bee Colonies: ENY2112/IN1431, 10/2024 - Gurland, Hannah N.; Fulton, James C.; Iredale, Marley E.; Vu, Amy T. (EDIS, 2024)
Digestive health is an overlooked but vital component of the success of Western honey bee (Apis mellifera) colonies. Viral, bacterial, fungal, and protozoal infections can inhibit nutrient uptake and waste elimination by the honey bee digestive tract. Active management requires monitoring honey bee health on an individual and colony basis, providing adequate nutrition, and controlling for other pests and diseases. One organism that has gained recent attention is Malpighamoeba mellificae. This publication describes how to detect M. mellificae in A. mellifera colonies.